Cultural dynamics and business strategies in international markets - Alegbeleye, Emmanuel Oluwaseun (Journal of Management and Business Education, 2025)
Through an analysis of cultural dynamics and global markets, this study probes the interplay of cultural and global influences on business strategy in the context of international expansion. Data are collected from 217 respondents through structured questionnaires that are distributed via Qualtrics, and the research uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze this data. The findings indicate a negative effect of perceived cultural barriers on business performance (β = -0.229), through cross-cultural communication (β = -0.249), indicating a need for a culturally adaptive communication strategy. On the one hand, the impact of cultural intelligence on market adaptability is significant (β = 0.618), but its direct effect on business performance is not significant, suggesting that market adaptability should be combined with other strategic efforts. the study also shows that cultural diversity enhances creativity without directly yielding competitive advantage as shown by its weak impact on purchase intention (β = -0.042). Finally, the study concludes that those businesses that embed cultural complexities and successfully manage them tend to have better results in the global market. It also points out that business schools should pay more attention to cultural intelligence. It gives real-world advice for developing course materials, preparing globally skilled experts, and helping business leaders adjust to cultural differences on a global scale.